1998
DOI: 10.1889/1.1833662
|View full text |Cite
|
Sign up to set email alerts
|

38.3: Predicting Color Breakup on Field‐Sequential Displays: Part 2

Abstract: We measured color-breakup thresholds for a simple field-sequential color stimulus while varying its luminance, contrast, and retinal velocity. Data analysis yielded an equation that predicts whether color breakup will be visible for specified viewing conditions. We compare this equation with an earlier version and discuss its uses and limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…This can yield the visual impression that colors in a moving object are spatially misaligned, a phenomenon called color breakup [23][24][25]. Color breakup occurs when colors are presented sequentially (as in single-chip DLP projectors [26,27]).…”
Section: Color Breakupmentioning
confidence: 99%
“…This can yield the visual impression that colors in a moving object are spatially misaligned, a phenomenon called color breakup [23][24][25]. Color breakup occurs when colors are presented sequentially (as in single-chip DLP projectors [26,27]).…”
Section: Color Breakupmentioning
confidence: 99%
“…5 Avoiding color break-up for RGB field-sequential displays in the presence of rapid eye movements requires color field rates well in excess of those needed to eliminate flicker and can easily exceed 1000 Hz when the display luminance and contrast are high. 6,7,8 The current "de facto" standard for sequential color field rates is in the range of 360-480 fieldsper-second, although many observers still perceive color break-up when viewing such displays with high-contrast, highluminance source material. 5,9 These high field rates impose severe bandwidth requirements on field-sequential displays and make the temporal isolation of primary color image fields very difficult.…”
Section: Field-sequential Color Projection Displaymentioning
confidence: 99%
“…Regarding the perceptual impact of the temporal component in such a hybrid spatial-temporal approach to color synthesis, prior research has found perceived color break-up is strongly determined by the luminance and contrast of the alternating color fields. 7,12 Since the R/G field contains both of the high luminance and high contrast components and alternates in time with the temporally diffuse and low luminance B field, perceived color break-up is largely mitigated and required field rates will primarily be determined by flicker. Temporal frequencies required to preclude observable flicker reach an asymptote at approximately 80 Hz even for fully modulated temporal waveforms at high levels of retinal illuminance.…”
Section: Synthesizing Colors In Both Space and Timementioning
confidence: 99%
“…Additional development work is needed to reduce this and other temporal artifacts in these types of digital displays, particularly for HMDs, where head motion may exacerbate the problem. These artifacts can be predicted when the temporal characteristics, and other properties of the display, are known (Lindholm & Scharine, 2000;Post, Nagy, Monnier, & Calhoun, 1998 Another promising display technology is the flexible flat panel. These displays are currently under development by a number of organizations (Crawford, 2004).…”
Section: Current Technologymentioning
confidence: 99%
“…No Yes Weight/ center gravity (cg) (including helmet or headband) < 3 lbs with cg < 2 inches in front of y-axis of head 8 < 4 lbs with cg < 2 inches in front of y-axis of head Keller and Colucci (1998); 8 Melzer & Moffitt (1997) *untested but based in part on data of Winterbottom et al (2004) may reduce motion blur by roughly 90%; **untested but based on data of Winterbottom et al (2004) may reduce motion blur by roughly 50%; ***untested but based on equation provided by Post et al (1998) should prevent noticable color break-up for speeds up to approximately 160 degrees/sec; ****untested but based on equation provided by Post et al (1998) should prevent noticable color break-up for speeds up to approximately 7 degrees/sec; † Partly an IG requirement, however refresh rate should match update rate (Lindholm & Martin, 1993); † † Current display refresh/update rate, display refresh rate should match IG update rate (Lindholm & Martin, 1993); Matching field of view of human visual system; Air…”
Section: Summary Of Hmd Characteristicsmentioning
confidence: 99%